2011
DOI: 10.1073/pnas.1102779108
|View full text |Cite
|
Sign up to set email alerts
|

Complementary roles of Fas-associated death domain (FADD) and receptor interacting protein kinase-3 (RIPK3) in T-cell homeostasis and antiviral immunity

Abstract: Caspase-8 (casp8) is required for extrinsic apoptosis, and mice deficient in casp8 fail to develop and die in utero while ultimately failing to maintain the proliferation of T cells, B cells, and a host of other cell types. Paradoxically, these failures are not caused by a defect in apoptosis, but by a presumed proliferative function of this protease. Indeed, following mitogenic stimulation, T cells lacking casp8 or its adaptor protein FADD (Fas-associated death domain protein) develop a hyperautophagic morpho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
107
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(118 citation statements)
references
References 39 publications
7
107
0
Order By: Relevance
“…In the context of a virus infection, activating PKR (either directly by virus RNA or indirectly via production of type I IFNs) can initiate necrosis in G 2 /M when FADD is phosphorylated and consequent PKR necrosome formation is licensed. In a similar manner, cells in which FADD/caspase expression or function have been compromised by virus infection [for example, by virally encoded inhibitors of apoptosis (31) Recent studies have shown that FADD-in addition to regulating IFN-activated necrosis as reported in this study-also controls the activity of RIP1/3 kinases to (i) restrict fulminant inflammatory tissue damage in the gut and skin, (ii) prevent inopportune T-cell necrosis during development and immune responses, and (iii) allow normal progression through embryogenesis (16,(32)(33)(34)(35)(36). In each of these scenarios, the upstream signals that activate RIP1/3 when FADD is absent remain vague (4).…”
Section: Discussionmentioning
confidence: 99%
“…In the context of a virus infection, activating PKR (either directly by virus RNA or indirectly via production of type I IFNs) can initiate necrosis in G 2 /M when FADD is phosphorylated and consequent PKR necrosome formation is licensed. In a similar manner, cells in which FADD/caspase expression or function have been compromised by virus infection [for example, by virally encoded inhibitors of apoptosis (31) Recent studies have shown that FADD-in addition to regulating IFN-activated necrosis as reported in this study-also controls the activity of RIP1/3 kinases to (i) restrict fulminant inflammatory tissue damage in the gut and skin, (ii) prevent inopportune T-cell necrosis during development and immune responses, and (iii) allow normal progression through embryogenesis (16,(32)(33)(34)(35)(36). In each of these scenarios, the upstream signals that activate RIP1/3 when FADD is absent remain vague (4).…”
Section: Discussionmentioning
confidence: 99%
“…Activity of RIPK1 and RIPK3, that modulate necrosis and autophagy, is limited by their cleavage by caspase-8, which results in limitation of autophagy and necrosis. Only in the absence of robust caspase-8 activity a stable complex between RIPK1 and RIPK3 is formed, promoting programmed necrosis and autophagy (instead of apoptosis) (Lu et al 2011). Death receptor signaling via RIPK1 and RIPK3 has also been studied in a model involving the assembly of DISC in isolated membranes/pre-autophagosomal structures (PAS).…”
Section: Other Interconnections Between Apoptotic Necrotic and Autopmentioning
confidence: 99%
“…Although FADD is found in the necrosome complex and is regarded as an adaptor protein that links DRs to the RIP1-RIP3 complex 9,31,32,42 , it appears to function as a negative regulator of necroptosis under various conditions 5,7,10,11,43 . To determine the exact function of FADD in necrosome formation in relation to MKRN1, we first depleted FADD in L929 and HT-29 cells.…”
Section: Fadd Stabilization Upon Mkrn1 Depletion Prevents Necroptosismentioning
confidence: 99%